The Effect of SARS-CoV-2 on the Gut and Its Microbiome: What We Know and What We Would Like to Know - N. V. Evdokimova; T. V. Chernenkaya (Неотложная медицинская помощь)
In the present review, we consider theoretical background and results of the first studies of SARS-CoV-2 effect on the intestine and its microbiome. The data obtained indicate the long-term virus persistence in the cells of intestinal mucosa. In addition, acceleration of microbial cells and microbial metabolites translocation associated with inflammatory processes in the intestinal endothelial cells caused by the virus was also discussed. COVID-19 has a great impact on structure and functional activity of the intestinal microbiome. The decrease in species diversity and minor species dominations that are not found in the microbiome of healthy controls were observed. The gut microbiome is considered to be an important influencer on COVID-19 progression and outcome.